Transvenous lead extraction with laser reduces need for femoral approach during the procedure - Younis, Arwa (PLoS One, 2019)
INTRODUCTION: Cardiac implantable electronic device (CIED) trans venous lead extraction (TLE) is technically challenging. Whether the use of a laser sheath reduces complications and improves outcomes is still in debate. We therefore aimed at comparing our experience with and without laser in a large referral center. METHODS: Information of all patients undergoing TLE was collected prospectively. We retrospectively compared procedural outcomes prior to the introduction of the laser sheath lead extraction technique to use of laser sheath. RESULTS: During the years 2007–2017, there were 850 attempted lead removals in 407 pts. Of them, 339 (83%) were extracted due to infection, device upgrade/lead malfunction in 42 (10%) cases, and other (7%). Complete removal (radiological success) of all leads was achieved in (88%). Partial removal was achieved in another 6% of the patients. Comparison of cases prior to and after laser technique introduction, showed that with laser, a significantly smaller proportion of cases required conversion to femoral approach [31/275 (6%) laser vs. 40/132 (15%) non-laser; p<0.001]. However, success rates of removal [259/275 (94%) vs. 124/132 (94%) respectively; p = 0.83] and total complication rates [35 (13%) vs. 19 (14%) respectively; p = 0.86] did not differ prior to and after laser use. In multivariate analysis, laser-assisted extraction was an independent predictor for no need for femoral extraction (OR = 0.39; 95% CI 0.23–0.69; p = 0.01). CONCLUSION: Introduction of laser lead removal resulted in decreased need to convert to femoral approach, albeit without improving success rates or preventing major complications.